2014
DOI: 10.5935/1808-8694.20140028
|View full text |Cite
|
Sign up to set email alerts
|

Auditory pathways’ maturation after cochlear implant via cortical auditory evoked potentials ✩✩Please cite this article as: Silva LAF, Couto MIV, Tsuji RK, Bento RF, Matas CG, Carvalho ACM. Auditory pathways’ maturation after cochlear implant via cortical auditory evoked potentials. Braz J Otorhinolaryngol. 2014;80:131-7.,✩✩✩✩Study conducted at work performed in the Departament of Phisotherapy, Phonoaudiology and Occupational Therapy and in Departament of Otorhinolaryngology, Faculdade de Medicina, Univers

Abstract: Changes in the characteristics of cortical auditory evoked potentials can be observed in children who receive cochlear implants; these changes are related to the age of intervention, suggesting a rapid maturation of the auditory pathways after electrical stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
4
1
1
Order By: Relevance
“…Contrary to this research, other studies 37 38 39 in which SPL did not correlate with age concluded that the factors affecting the performance of cochlear implant users in speech perception tests are the earlier activation of CI and the use of hearing aids in the contralateral ear. …”
Section: Discussioncontrasting
confidence: 95%
“…Contrary to this research, other studies 37 38 39 in which SPL did not correlate with age concluded that the factors affecting the performance of cochlear implant users in speech perception tests are the earlier activation of CI and the use of hearing aids in the contralateral ear. …”
Section: Discussioncontrasting
confidence: 95%
“…These children were compared with their peers of same age with normal hearing to verify whether there was proper development of the auditory pathway in individuals in the study group. The authors concluded that the latency values of the wave P1 in implanted children after three months of CI activation is higher than that of normal-hearing children, with reduction occurring at four years of age (23) . Still with regard to the analysis of the results presented in Table 1, data from the Preterm Group are similar to those observed in another study (14) on the use of other electrophysiologic measure, BAEP, in neonates considered small for gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the auditory stimulation of deaf children before 36 months of age allows a very fast maturation of auditory system [ 8 , 28 , 29 ]. After this period, the development occurs differently from that of hearing children [ 8 , 14 , 20 ].…”
Section: Discussionmentioning
confidence: 99%